(untitled) (Journal of Nepalese Business Studies, 2021)
Vietnam’s policy of openness to trade and investment has made it integrated very quickly with the global production networks, also known as global value chains, which has brought many visible fortunes to it in terms of socio-economic achievements. To have a deeper insight into the prospects and constraints of its integration into global value chains, and also to assess its degree of integration, this paper has employed Koopman et al. (2010) approach to measure the participation index, and position index. The analysis shows that the participation of Vietnam in global value chains has increased significantly in the last two decades based on strengthening FDI-led exports of Vietnam. It also shows that most of the exporting industries are located in the middle-stream in the value curve and are net buyers of intermediate products for exports, which infers the presence of predominant I2E practices in Vietnam. The paper also identifies and assesses the risk I2E practices are prone to. Scenario analysis suggests that Vietnam shall focus on upskilling of its labour force and developing indigenous industrial base. In the meantime, domestic firms shall be encouraged to collaborate with foreign firms and densify into global value chains.